Pengaruh Budaya dan Sosial dalam Pengembangan Desain Batik Langgam Medan - Damanik, Raudhotul Jannah; Fitri, Hadiani; Hardiansyah, Muhammad Ricky (Polyscopia, 2025)
This study employs qualitative methods with a historical approach to analyze the influence of culture and society on the development of Batik Langgam Medan design. The historical approach is used to systematically collect and evaluate data related to past events that have shaped the evolution of Batik Langgam and its future potential. The findings reveal that Batik Langgam was established in 2008 by Hj. Rafika Johani, S.Ag., with the name "Langgam," meaning style, model, as well as ideas and creations derived from the local wisdom of North Sumatran ethnic groups. Initially, Batik Langgam specialized in producing souvenirs and batik featuring traditional North Sumatran motifs. The history and evolution of Batik Langgam have been significantly influenced by both Malay and Javanese cultures. The motifs of Batik Langgam Medan represent local adaptations of Javanese batik, incorporating elements of Malay heritage, Batak motifs, and environmental influences such as geometric and floral patterns. This study concludes that Batik Langgam Medan serves as a dynamic representation of cultural interaction, reinforcing its role as a symbol of evolving cultural identity in response to social and economic changes.